PERLINDUNGAN HUKUM BAGI NASABAH DALAM TRANSAKSI GADAI OLEH LEMBAGA GADAI SWASTA YANG BELUM MEMILIKI IZIN DI INDONESIA - Resti Remandha; Pranoto Pranoto (Jurnal Privat Law, 2026)
This article aims to analyze and examine the legal protection for customers in pawn transactions by private pawnshops that do not have a license in Indonesia which is expected to provide insight for the wider community. This research is a prescriptive normative legal research with a statutory approach and a conceptual approach. The type of data used is secondary data which includes primary legal materials and secondary legal materials. While the data collection technique in this research is by using the method of browsing through the internet media which is then followed by analysis techniques using grammatical, historical, and systematic interpretation techniques. The results of this study indicate that the legal protection obtained by customers who use pawn transactions at private pawn institutions that do not yet have a permit is based on the agreement made by the pawning institution with the customer itself. Although they do not get protection from the Financial Services Authority as the supervisor of the pawning institution, customers get legal protection based on the laws in force in Indonesia. If the customer is harmed due to a default or unlawful act committed by the private pawnshop, the customer has the authority to file a lawsuit to the local District Court and if there are criminal elements such as fraud or embezzlement, the customer can also report the act to the Police. Thus, customers have legal protection and legal certainty to achieve justice.